Stomach carcinoma in the Indian subcontinent: A 16-year trend - Cherian Jijo; Sivaraman Ramalingam; Muthusamy Arun; Venkataraman Jayanthi (The Saudi Journal of Gastroenterology, 2007)
Background: Gastric malignancy is one of the most common causes for cancer-related deaths. Reports from the west have shown a paradigm shift in the site of occurrence with malignancies of the gastric cardium increasing in frequency, reports which are contrary to information from the Middle East and South Asia. Aim: To determine trend changes in distribution of gastric malignancy between 1989 and 2004 in the southern state of Tamil Nadu in India. Materials and Methods: The study period was divided into four cohorts of four years each (1989-1992, 1993-1996, 1997-2000 and 2001-2004) for the analysis of the changes in trend for subsite specificity, age and gender predilection. Results: Clinically, there were no significant differences in the presenting symptoms or physical signs in the four cohorts. The antrum was the most common site of predilection, no site-specific change was noted and males continued to be more commonly affected of the two sexes. Gastric cancer was significantly higher above the age of 40 years in all the four subsites and cohorts. A decrease in the mean age was observed for men with cancers of the esophagogastric junction (OGJ) ( P < 0.0001) and the proximal stomach ( P < 0.0001), while junctional malignancy ( P < 0.0001), cancers of the proximal stomach ( P < 0.0001) and the antrum ( P = 0.03) tended to occur progressively later among women. Conclusion: No change in site specificity or gender predilection for gastric adenocarcinoma has been noted in the past 16 years. However, a gender-dependent paradigm shift in the mean age of presentation is discernible for cancers involving the OGJ, proximal stomach and antrum.